- #1

seang

- 184

- 0

Hello, I'll be online until I get this one completely figured out, so baby steps are for the win here.

Let L1:U->V and L2:U->W be linear transformations, and let L = L2 * L1 be the mapping defined by:

L(u) = L2(L1(u))

for each u which lies in U. Show that L is a linear transformation mapping U into W.

So basically, should I first show that L1(u) is a valid linear transform?, and then show that L2, is, too?

Let L1:U->V and L2:U->W be linear transformations, and let L = L2 * L1 be the mapping defined by:

L(u) = L2(L1(u))

for each u which lies in U. Show that L is a linear transformation mapping U into W.

So basically, should I first show that L1(u) is a valid linear transform?, and then show that L2, is, too?

Last edited: